Digitalisasi Proses Pendaftaran Calon Santri SMK Skill Village Islamic School Jonggol - Bogor - Jawa Barat - Jundi Kariman Husni; Obed El-Fatih Syams; Ziyad Fernanda Syams (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This research develops a new website-based student registration system for SMK Skill Village Islamic School to overcome the obstacles of inefficient conventional registration. This system is built using PHP, Laravel, Bootstrap, and MySQL, providing a dashboard for admins and prospective students. Admins can manage registrant data, while prospective students can fill out forms, upload proof of payment, and requirement files online. This system is expected to increase the efficiency and effectiveness of the registration process.